CULTURAL INDUSTRY 4.0: A CRITIQUE OF PERSONAL BRANDING AND THE COMMODIFICATION OF IDENTITY IN THE DIGITAL INFLUENCER ECOSYSTEM - Harahap, Mhd. Harvinsyah Rozi; Ritonga, Hasnun Jauhari; Tanjung, Ahmad Sujai (Journal Analytica Islamica, 2026)
The rapid expansion of digital communication technologies has transformed identity into a strategic and economic asset within platform capitalism. Social media influencers and infotainment media increasingly operate within a system where personal branding becomes central to symbolic production and market exchange. This study aims to critically analyze the commodification of identity in the influencer ecosystem and televised infotainment through the lens of Critical Communication Theory. Employing a qualitative embedded case study approach, the research examines selected Indonesian Instagram and TikTok influencers alongside RCTI Infotainment broadcasts. Data were collected through systematic digital documentation, audio-visual transcription, and structural contextual review, and analyzed using thematic coding and critical interpretive analysis grounded in the culture industry thesis and digital capitalism theory. The findings reveal that curated authenticity, emotional dramatization, and commercial integration are structured by algorithmic governance and engagement metrics, transforming subjectivity into a monetizable commodity. Both digital influencers and broadcast infotainment demonstrate structural continuity in reproducing instrumental rationality and neoliberal market logic. The study contributes to the expansion of the culture industry concept into Culture Industry 4.0, where identity itself becomes the primary unit of economic production. It concludes that personal branding is not merely an individual communication strategy but a structural mechanism embedded in digital capitalism, with implications for media ethics, identity formation, and critical communication scholarship. Future research is encouraged to incorporate audience reception analysis and comparative cross-platform studies to further explore dynamics of power and resistance in digital culture.